Metode FMECA (Failure Modes, Effect, and Criticallity Analysis) untuk Penentuan Prioritas Pemeliharaan dan Pencegahan Gangguan pada Penyulang 20 kV di Wilayah Kerja PT. PLN (Persero) ULP Karebosi - Sultan, Ahmad Rizal; Bachtiar, Muhammad Imran; Wafa, Habib Yardan (Jurnal Teknologi Elekterika, 2023)
Failure Modes, Effect, and Criticality Analysis is an analytical method to determine the cause of disturbance on 20 kV feeders in Unit Layanan Pelanggan Karebosi’s area of responsibility that will be used later to prioritize maintenance and prevention efforts. To determine the priority, the rating of severity, occurrence, and detection of each cause of disturbance recorded during the 2022 period is needed to be known beforehand. The cause of disturbance is prioritized based on the results of RPN (Risk Priority Number) and Criticality Analysis. Causes of disturbance that need to be prioritized for maintenance and prevention efforts are medium-voltage equipment, medium-voltage components, natural disasters, and third-party activity. The result from this analysis is to be used for reliability improvement planning in the future